An Australian Perspective on Singaporean Welfare Policy - Philip Mendes (Social Work & Society, 2007)
From a Western perspective, Singapore appears to be an overt example of a neo-liberal welfare regime based on low social expenditure, and limited and discretionary social assistance. But the true picture is arguably more complex. Singapore's welfare policy is driven by strong cultural assumptions around individual and family self-reliance, and the inappropriateness of state welfare provision. However, there is also a strong emphasis on communal responsibility for supporting the disadvantaged. Some conclusions are drawn about the limitations of existing policies, and possible new directions for the future.